Utility of Epworth Sleepiness Scale (ESS) in predicting the presence of Sleep Related Breathing Disorders (SRBD) in patients in Routine Respiratory Clinical Service - Koirala, Puru; Ghimire, Ram Hari; Mishra, Deebya Raj; Bista, Bidesh; Shah, Bhupendra (Journal of Nobel Medical College, 2018)
Background : Many patients attending routine respiratory clinical service in developing countries also present with complains of daytime sleepiness and sleep abnormalities. A large proportion of them might have Sleep Related Breathing Disorders (SRBD) and as such, it is underestimated. Within this background we conducted a study to explore the presence of SRBD among patients presenting with symptom complex of respiratory diseases in Routine Respiratory Clinical Service by use of Epworth Sleepiness Scale (ESS). Material and Methods: A cross-sectional study of 50 patients with respiratory symptom complex was conducted in respiratory clinical service of Division of Pulmonary, Critical Care and Sleep Medicine at B. P. Koirala Institute of Health Sciences (BPKIHS) from 2014-2015. Targeted Comprehensive Sleep History and Epworth Sleepiness Scale (ESS) were used to recognize the presence of SRBD among these patients. Results: 74% patients had ESS score ≥10. Mean ESS was 12.32 (±4.76). 72% subjects had daytime fatigue, 62% loud snoring, 58% daytime sleepiness and 46% sleep fragmentation. ESS ≥10 reflected excessive daytime sleepiness (sensitivity 86.67%; 95% CI, 69.28 – 96.24; specificity 45%, 95% CI, 23.06 – 68.47; PPV 70.27%, 95% CI, 53.02 – 84.13; NPV 69.23%, 95% CI, 38.57 – 90.91). Conclusion: Epworth Sleepiness Scale has utility in predicting SRBD in patients with respiratory symptom complex with high overall predictive accuracy. It can be used in routine clinical care to identify and predict patients having Sleep Related Breathing Disorder and refer them to clinical sleep services for further evaluation. Journal of Nobel Medical College Volume 6, Number 2, Issue 11 (July-December, 2017) Page:9-13